Synthetic niclosamide-loaded controlled-release nanospheres with high solubility and stability exerting multiple effects against Clostridioides difficile - Tai, Yulei; Zhang, Meng; Han, Yuning; Hu, Hui; Lin, Shan; Zhai, Fangya; Tian, Menglun; Song, Xiaojun; Wan, Shuangshuang; Chen, Yu; Jin, Dazhi (Frontiers in Microbiology, 2025)
IntroductionNiclosamide (NIC) has significant potential as a clinical therapeutic agent for Clostridioides difficile infection (CDI); however, its strong hydrophobicity hampers its oral bioavailability, and its active effects against C. difficile remain unclear.MethodsNiclosamide-loaded controlled-release hyaluronic acid-modified poly (lactic-co-glycolic acid) naosphernes (NIC@PLGA-HAs) were synthesized using an oil-in-water emulsion technique and their effects on C. difficile cell growth, spore germination, biofilm formation, and NIC interaction sites with C. difficile toxin B (TcdB) were analyzed.ResultsNIC@PLGA-HAs exhibited enhanced solubility and stability, with a water contact angle on a hydrophilic surface of 65.1° and a zeta potential of 31.57 ± 2.08 mV, and pH-responsive (pH 7.4) controlled-release characteristics compared to free NIC. The NIC@PLGA-HAs killed C. difficile vegetative cells at a minimum inhibitory concentration (MIC) of 4 μg/mL. When C. difficile cells were treated with NIC@PLGA-HAs at the 1/4 MIC, spore germination and biofilm formation were significantly inhibited compared to those in untreated cells (P < 0.01). NIC was found to interact with the receptor-binding domain of TcdB at 24 amino acid sites via an enthalpy-driven reaction (enthalpy change, 36.21 kJ/mol and entropy change, 212.9 J⋅mol/K). In vivo experimental findings in Mongolian gerbils indicated that NIC@PLGA-HAs outperformed free NIC in reducing pathological damage, diarrhea severity, weight loss, and TcdB production and enhanced the survival rate.ConclusionThese findings presented the therapeutic potential of NIC@PLGA-HAs with high solubility and stability, which simultaneously exerted multiple biological activities against C. difficile.